Pengaruh Residu Biochar Sekam Padi dan Pupuk Kandang Sapi terhadap N Total dan Serapan N oleh Tanaman Jagung (Zea mays L.) - Slamet Supriyadi; Fahmi Arief Rahman; Erick Yuhardi; Rika Devi Rahmah (Jurnal Agroekoteknologi, 2023)
The objective of this study was to investigate the effects of soil conditioner of residue of rice husk biochar and cow manure, which was applied one year before this research conducted, on total N content in the soil and N uptake by maize (Zea mays L.). The research was carriet out at the Socah Horticultural Garden, Bangkalan Regency, East Java, which is located at 5-meter above sea level, from November 2020 to March 2021. The experiment was arranged on a completed randomized block design (CRBD), consisting of six treatments, namely P0 (control, without biochar or cow manure), P1 (10 ton biochar/ha), P2 (7.5 ton biochar/ha and 2.5 ton cow manure/ha), P3 (5 ton biochar/ha and 5 ton cow manure/ha), P4 (2.5 ton biochar/ha and 7.5 ton cow manure/ha), P5 (10 ton cow manure/ha). The results showed that Rice husk biochar residue and cow manure had a significant effect on total N in P4, organic carbon in P5, and CEC in P3 but that not significantly different with P2 and P4. While treatments that significantly affect N in plant tissues and N uptake by corn plants are P4.